What is known and unknown about the role of neuroendocrine genes Ptprn and Ptprn2 - Stojilkovic, Stanko S.; Sokanovic, Srdjan J.; Constantin, Stephanie (Frontiers in Endocrinology, 2025)
The protein tyrosine phosphatase receptors N and N2 are encoded by the Ptprn and Ptprn2 genes expressed in neuroendocrine cells of the hypothalamus, pituitary gland, and diffuse neuroendocrine system, including the pancreas, lung, and intestine. Unlike other members of the protein tyrosine phosphatase receptor family, PTPRN and PTPRN2 lack protein tyrosine phosphatase activity due to mutation of two residues in their intracellular catalytic domains. However, during evolution these proteins acquired new cellular roles beyond tyrosine dephosphorylation in the centralized and diffuse neuroendocrine systems. Here we discuss the current understanding and lack of information about the actions of these proteins, focusing on neuroendocrine cells of the hypothalamus, pituitary, and pancreas.